Application of DEA for Evaluating the Efficiency of Economic Policy as Exemplified by EU Agriculture - Błażejczyk-Majka, Lucyna (Studia Historiae Oeconomicae, 2017)
The article presents how DEA is used to develop agricultural production efficiency rankings in the EU member states, which can be used as the starting point for evaluating the performance of currently used instruments of economic policy. In the article, statistical data from the FADN were used. Agricultural production was compared for three types of output and four types of input involved. The performed study demonstrated that in 18 out of 28 states, agricultural production had been run efficiently on a macro level. The applied approach also allowed for identifying the causes of inefficiency in the remaining ten states, providing indications for recommended changes in in the way economic instruments are used.